Randomised clinical study: inulin short‐chain fatty acid esters for targeted delivery of short‐chain fatty acids to the human colon. Issue 7 (28th July 2016) - Polyviou, T.; MacDougall, K.; Chambers, E. S.; Viardot, A.; Psichas, A.; Jawaid, S.; Harris, H. C.; Edwards, C. A.; Simpson, L.; Murphy, K. G.; Zac‐Varghese, S. E. K.; Blundell, J. E.; et al.
Summary: Background: Short‐chain fatty acids (SCFA) produced through fermentation of nondigestible carbohydrates by the gut microbiota are associated with positive metabolic effects. However, well‐controlled trials are limited in humans. Aims: To develop a methodology to deliver SCFA directly to the colon, and to optimise colonic propionate delivery in humans, to determine its role in appetite regulation and food intake. Methods: Inulin SCFA esters were developed and tested as site‐specific delivery vehicles for SCFA to the proximal colon. Inulin propionate esters containing 0–61 wt% (IPE‐0–IPE‐61) propionate were assessed in vitro using batch faecal fermentations. In a randomised, controlled, crossover study, with inulin as control, ad libitum food intake (kcal) was compared after 7 days on IPE‐27 or IPE‐54 (10 g/day all treatments). Propionate release was determined using 13 C‐labelled IPE variants. Results: In vitro, IPE‐27–IPE‐54 wt% propionate resulted in a sevenfold increase in propionate production compared with inulin ( P < 0.05). In vivo, IPE‐27 led to greater 13 C recovery in breath CO2 than IPE‐54 (64.9 vs. 24.9%, P = 0.001). IPE‐27 also led to a reduction in energy intake during the ad libitum test meal compared with both inulin (439.5 vs. 703.9 kcal, P = 0.025) and IPE‐54 (439.5 vs. 659.3 kcal, P = 0.025), whereas IPE‐54 was not significantly different from inulin control. Conclusions: IPE‐27 significantly reduced food intake suggesting colonic propionate plays a role in appetite regulation. Inulin short‐chain fatty acid esters provide a novel tool for probing the diet–gut microbiome–host metabolism axis in humans.